How ethical leadership is related to authenticity - Florian Demont-Biaggi (Leadership, Education, Personality. An Interdisciplinary Journal, 2019)
In this conceptual paper, I shall explain one concrete way of defining ethical leadership, namely authentic leadership. After a description of the ethical components some canonical proponents envisage, objections from the recent literature will be discussed. The main focus will be on how the concept of authenticity helps us to better understand ethical leadership. The central line of thought is this: If we construe authenticity in interactional and processual terms, where leadership is seen as a process of interaction between people in concrete contexts, then we may identify patterns of leadership development through which we can make sense of how authenticity and ethics are related. In the end, as will be argued, these patterns have one pivot: authenticity and ethics come together in a leader's moral conscience. But moral conscience also has important implications on the level of interactions between people in groups and thus affect how ethical leadership influences followers and organizational structures. It is this last thought, which will conclude the article.
Keywords: 330; Leadership ethics; Authentic leadership; Philosophy of leadership; Moral conscience